A Perfect Accord: Music and Gesture in Francis Poulenc’s Les Biches - Moore, Christopher (Les Cahiers de la Société québécoise de recherche en musique)

(untitled) (Société québécoise de recherche en musique, 2012)
The critical reception surrounding the ballet Les Biches (1924) reveals that the work’s initial success was largely attributable to the aesthetic synergies that unified the musical and gestural components of the work. Indebted to musical and visual themes derived from high-society fashion, and receptive to the aesthetic lure of contemporaneous (and specifically Stravinskian) neoclassical experiments, Francis Poulenc’s music and Bronislava Nijinska’s choreography display complementary approaches towards the artistic juxtaposition of past and present. This article draws on the reception of both the Monte Carlo and Parisian premieres of this Ballet russes production and emphasizes how Les Biches constituted a landmark achievement in Poulenc’s musical development and early career.